The evaluation of opportunities for the development of access for charging electric vehicles in the territory of apartment buildings - Palevičius, Vytautas; Karpavičius, Tomas; Kaušylas, Mantas (International Conference “Environmental Engineering”, 2017)
The beginning of 21th century is extremely important for developed countries because of the reduction of their dependence on fossil fuels. The biggest vehicle manufacturing companies are planning to start selling at least one model of electric vehicle and it is expected that by 2025 approximately 10% of the new cars sold worldwide will be electric. In order to reach this goal, some countries are successfully executing an effective electric transport development policy: to create a publicly accessible network for charging electric vehicles, pay incentives for purchasing an electric car, create free of charge parking places and implement other encouraging measures. While analysing world trends it has been noted that the majority of electric cars owners live in private houses. This is due to the fact that people who are living in apartment buildings and planning on purchasing an electric car come across multiple issues when it comes to charging the car at their living area at night. Therefore, the aim of this article is to evaluate the opportunities of developing access points for charging electric cars around the territory of apartment buildings. To achieve this we have raised these main objectives: have the EU member states already foreseen the necessary measures ensuring comfortable charging of electric cars in the territory of apartment buildings?; have the plans for the development of charging facilities in the territory of apartment buildings already been prepared?; which new technologies will be used for the safe charging of electric cars?